Distributive Politics, Nature of Government Spending and Economic Growth in a Low Income Democracy - Sasmal, Joydeb (2011)
In this paper we analyze how the government in a democratic setup of the developing world manipulates the fiscal instruments to maximize its political gain so that it can retain power. The government and the voters in low income countries are generally selfish and myopic in the sense that the electorates prefer to get direct and immediate benefits from the government while the government, in turn, tries to seek majority support in the election, by adopting short term and distributive policies instead of going for long term growth. Using the theoretical structure of the existing literature, and making modifications therein, this study demonstrates that the optimal tax rate, public expenditure shares and growth rate are determined in terms of technological and behavioral parameters. The simulation results show that if political gain from distributive policies is high, the government will allocate a greater share of the fund for distributive purposes adversely affecting economic growth.